Unrealized Screenplay by Vojtěch Jasný - Voráč, Jiří (Iluminace, 2003)
The introduction to Vojtěch Jasný's literary screenplay Kominíček a korouhvičky presents the history of the screenplay.
Keywords: literary script; unrealised scripts; director's illustrations; history of the project; Vojtěch Jasný